PERANAN GURU PPKN DALAM MEMBINA KESADARAN MORAL SISWA SMK AL-QU’AN DAN DAKWAH ALAM DI KRINCING - Fiki, Fiki; Hadi, Agustinus Sutriyanto; Srihadi, Srihadi (Journal of Democratia; Vol 2 No 02 (2024): Jurnal Democratia Pendidikan Pancasila dan KewarganegaraanDO - 10.31331/jade.v2i02.3251, 2024)
This research is a qualitative research, using data collection techniques  through observation, interviews, and documentation. In conducting data analysis, researchers used data analysis techniques proposed by Miles and Huberman, where each component includes data reduction, data presentation, and drawing conclusions. These findings lead to the conclusion that the role of Civics teachers in fostering students' moral awareness is: setting a good example, applying discipline, mutual respect, and providing a fair attitude in learning. The obstacles faced by PPKn SMK ADA Krincing teachers in fostering students' moral awareness are: The effect of the lack of hours of study, the lack of cooperation between the school and the parents of students, the indifference of students, discipline and attendance of students in taking lessons. Some of the efforts of ADA Krincing VOCATIONAL SCHOOL PPKn teachers in fostering the moral awareness of SMK students, namely: Providing attention, good advice and motivation, providing input that builds awareness and enthusiasm that the importance of collaboration between schools and parents, providing special attention and advice in the form of coaching and guidance, and it is hoped that other teachers will also participate in fostering student moral awareness.